System enhancement : Sistem Amanah Tugas Akademik (SATAv2) /Mohd Helmi Hashim - Hashim, Mohd Helmi (2014)
This research aims to enhance the lecturer workload system which is Sistem Amanah Tugas Akademik (SATA), which is currently executed in Universiti Teknologi MARA (UiTM) (Terengganu). Main purpose of this research is to solve the current problems that involved the data mistakenly recorded into the system. The time tabling committees is the main users of this system. As the result, this research come out with a prototype system that incorporate of one faculty which is Fakulti Sains Komputer dan Matametik (FSKM) that include two departments which are Computer Sciences department and Mathematics department. The ability of the prototype system is simplifying the data entry method and improves the certain interface on it. The result of this research is the comparison between the current system and the enhancement system. For the future enhancement, the system can be focus on minimize more on user selections menu such as more filtering at item to select the classroom and lecture type. Other than that, the future enhancement can be made by directly link to the system that generates time table slot that known as iCress.